RI 7827 Distribution of Sulfur and Ash in Part of the Pittsburgh Seam and Probable Mode of Deposition - Manuel Gomez (The National Institute for Occupational Safety and Health (NIOSH), 1974)
Areal distributions for ash, total sulfur, and sulfur forms were developed for the top 12 inches, the middle section, the bottom 8 inches, and the total seam of Pittsburgh coal in southwestern Pennsylvania. The sulfur and ash exhibit an apparent high local variability. As a general rule, both the sulfur and ash show high concentrations in the top 12 inches and in the bottom 8 inches of the seam relative to the concentrations observed in the middle section of the seam. The high-low sulfur and ash concentrations in the top 12 inches of the seam are not coincident with the high-low sulfur and ash concentrations in either the middle section or the bottom 8 inches of the seam. With respect to sulfur and ash, it is suggested that the top and bottom sections of the Pittsburgh coal may reflect both a syngenetic and epigenetic origin. Present data support the belief that paleotopography controlled Pittsburgh seam deposition. Evidence is presented to show that channels were cut at various times into the semilithified sediments that buried the Pittsburgh seam. In this channeling process, portions of the Pittsburgh coal may have been eroded away. Following channel development, the lower part of the Pittsburgh sandstone filled the complex system of braided channels to produce the "want areas" encountered in present mining operations. In localized areas of the Pittsburgh seam, impingement of Pittsburgh sandstone may be responsible for the lateral displacement of the coal. Information of this type becomes important in the assessment of exploration data, in the development of a quality control system for mine output, and in mine life planning.